Etika Penggunaan Artificial Intelligence (AI) dalam Administrasi Publik: Telaah Perkembangan dan Tantangannya - Ahmad Difa Awlia Aslim; Nurul Ayuni; Andi Adhe Amalya (Public Inspiration : Jurnal Administrasi Publik, 2026)
The rapid development of digital technologies has significantly transformed public administration, particularly through the increasing adoption of Artificial Intelligence (AI) to enhance efficiency, service delivery, and evidence-based policymaking. Despite its potential benefits, the use of AI in the public sector raises complex ethical concerns related to transparency, algorithmic bias, privacy protection, and accountability, which remain insufficiently addressed in existing practices. This article aims to examine the development of AI implementation in public administration and to analyze the major ethical challenges associated with its use. The study employs a literature review approach by systematically analyzing academic journals, policy documents, and reports from international organizations published over the last decade. The findings indicate that while AI has been widely utilized for administrative automation, decision support, and data analytics, its implementation is often constrained by ethical risks, limited regulatory frameworks, institutional capacity gaps, and organizational resistance. The review highlights that issues of algorithmic fairness, explainability, data privacy, and responsibility for AI-based decisions are the most prominent ethical challenges. This study concludes that the effective and legitimate use of AI in public administration requires robust ethical governance frameworks that emphasize transparency, accountability, human oversight, and the protection of public values.